Financial Feasibility of Service-Based Business: A Case Study of Mengasihi Group - Hermawan, Zakaria Khori (Journal Integration of Social Studies and Business Development, 2024)
In Indonesia, over 6,300,000 toddlers are affected by stunting. Research indicates that the prevalence of stunting among children of working mothers is 30.6%. Despite the associated health risks, many working mothers prefer formula milk as a substitute for breast milk. Mengasihi, a health technology start-up providing breast milk powdering services for personal use, aims to offer babies a simple and effective nutritional solution. This study investigates the financial feasibility of Mengasihi as an early-stage start-up. It was found that cash flow plays a crucial role in start-up failure, impacting long-term organizational success. A feasibility study assessed Mengasihi's financial viability, analyzing internal and external financial conditions using criteria such as Payback Period, Net Present Value (NPV), and Internal Rate of Return (IRR) based on five-year financial projections. The results indicate that the Mengasihi project is financially viable, and an implementation plan was provided as part of the study.